ANALISIS MITIGASI NON STRUKTURAL KEBAKARAN DALAM UPAYA PENCEGAHAN BENCANA KEBAKARAN DI GEDUNG BERTINGKAT PERKANTORAN X JAKARTA - Vina Alzahra; Baju Widjasena; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Buildings X Jakarta is a skyscraper with a height of 75 meters. Ina fire situations, fire spread relatively quick. In buildings, extinguishing and rescue efforts will hardly executed because of limited access enter and exit of the building. It is cause multy-storey building be prone to fire. One of efforts to reduce the risk and impact caused by the fires is require the application of non-structural mitigation in multi-storey office building. The purpose of the study is to analyze non structural fire mitigation of prevention effort of fire disaster in multy-storey office building. This research is a Descriptive Qualitative research that produces words written or spoken of those who observed with in-depth interviews. The subjects of this study consists of 4 people as the main informants and 2 people as informant triangulation. The results show management has established written and date policies and commitment and signed by top management. Fire fighting training has not been given to all employees. Budgeting system for non-structural mitigation program has been budgeted annually. The procedure used when emergencies are simulated fire scenarios used. When emergencies have a communication system for notifying and requesting assistance to related parties. The conclusion of this study is building X Jakarta has adopted the non-structural mitigation programs such as simulation of fire, fire prevention policy dissemination, and training blackouts and evacuation of casualties. However, the implementation of the program had not maximized.